KETERLIBATAN KELUARGA DALAM PENGEMBANGAN BAHASA ANAK BERKEBUTUHAN KHUSUS DI USIA DINI - Riskiyah, Minda; Depalina, Syamsiah (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Language development is an important aspect in children's growth and development, especially for children with special needs at an early age who require more intensive support. This study aims to explore the role and involvement of families in the process of language development of children with special needs. The methods used include interviews with parents and observations of daily activities. The results of the study indicate that family involvement, both in the form of daily verbal interactions, assistance in therapy, and the provision of a supportive environment, contributes significantly to improving children's language skills. Factors such as parental knowledge, frequency of interaction, and cooperation with professionals also influence the effectiveness of this involvement. These findings emphasize the importance of the role of families as active partners in early intervention for the language development of children with special needs.